2000
DOI: 10.1177/0095798400026004004
|View full text |Cite
|
Sign up to set email alerts
|

Drug Attitudes, Racial Identity, and Alcohol Use among African American Adolescents

Abstract: This research examined relationships among four variables, including (a) participation in a culturally based prevention program, (b) changes in drug attitudes, (c) changes in racial identity, and (d) changes in alcohol use. The sample included 311 African American sixth graders (56% male) enrolled in a national study of high-risk youth. Participants completed the Children’s Racial Identity Scale, the Africentric Values Scale for Children, the Tentative Drug Use Scale, the Children’s Social Desirability Scale, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 33 publications
(35 reference statements)
1
20
0
Order By: Relevance
“…Moreover, higher numbers of our 8th graders than the Monitoring the Future sample acknowledged prior use of tobacco and marijuana (Johnston et al 2008b). Finally, as previously reported (Burlew et al 2000), the low correlation between the substance use measure and the Children's Social Desirability Scale in our sample also provides confidence in the quality of the self-report data.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, higher numbers of our 8th graders than the Monitoring the Future sample acknowledged prior use of tobacco and marijuana (Johnston et al 2008b). Finally, as previously reported (Burlew et al 2000), the low correlation between the substance use measure and the Children's Social Desirability Scale in our sample also provides confidence in the quality of the self-report data.…”
Section: Discussionsupporting
confidence: 85%
“…Those EBTs that have been tested generally fall into one of two categories. Some EBTs have demonstrated effectiveness for specific ethnic groups (Burlew, Burlew, Peteet, Johnson, & Smith, 2010; Huey & Polo, 2008; Miranda, Azucar, Organista, Dwyer, & Areane, 2003; Szapocznik, Prado, Burlew, Williams, & Santisteban, 2007). Others have been demonstrated to be ineffective for specific ethnic minority groups (Calsyn et al, 2012).…”
Section: Challenges To Cultural Adaptationmentioning
confidence: 99%
“…A related issue is that many interventions developed by and for ethnic minorities have not been able to obtain the funding to conduct the expensive Randomized Clinical Trials (RCTs) to meet the criteria to be classified as an EBT. In fact, when reviewing the literature for a paper on best treatments for ethnic minorities (Burlew et al, 2010), we identified numerous promising substance abuse prevention and treatment interventions that clinicians currently cannot select for their settings because the interventions have not been subjected to RCTs. Instead, a disproportionate number of these projects may be financed locally or funded by SAMSHA where the emphasis on service rather than research makes it difficult to fund RCTs.…”
Section: Social Work Implicationsmentioning
confidence: 99%
“…Another identity construct similar to ethnic group affiliation, racial identity, is also evidenced to be related to anti-drug attitudes and lowered alcohol use among African-American children and adolescents (Belgrave, Brome, & Hampton, 2000;Belgrave et al, 1994;Burlew, Neely, & Johnson, 2000;Townsend & Belgrave, 2000). For example, Townsend and Belgrave (2000) examined the relationship between racial identity and the drug attitudes and behaviors of 104 fourth graders.…”
Section: Ethnic Identitymentioning
confidence: 99%